Length–weight and length–length relationships of five fish species collected from seagrass beds of the Sungai Pulai estuary, Peninsular Malaysia - Arshad, Aziz; Jimmy, A.; Nurul Amin, Sanker Mohammad; Bujang, Japar Sidik; Zakaria, Muta Harah (2008)
Length–weight relationships are presented for five fish species from the seagrass beds of Peninsular Malaysia.